2009
DOI: 10.2337/dc09-1305
|View full text |Cite
|
Sign up to set email alerts
|

Subjects With Early-Onset Type 2 Diabetes Show Defective Activation of the Skeletal Muscle PGC-1α/Mitofusin-2 Regulatory Pathway in Response to Physical Activity

Abstract: OBJECTIVEType 2 diabetes is associated with insulin resistance and skeletal muscle mitochondrial dysfunction. We have found that subjects with early-onset type 2 diabetes show incapacity to increase Vo2max in response to chronic exercise. This suggests a defect in muscle mitochondrial response to exercise. Here, we have explored the nature of the mechanisms involved.RESEARCH DESIGN AND METHODSMuscle biopsies were collected from young type 2 diabetic subjects and obese control subjects before and after acute or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
121
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(138 citation statements)
references
References 24 publications
13
121
3
1
Order By: Relevance
“…Here, we demonstrate that Mfn2 deficiency in mice induces susceptibility to develop insulin resistance in response to both age and HFD treatment. These data fit with the observations that muscle Mfn2 is repressed in human obesity or in type 2 diabetes (13,14) and allow us to propose that Mfn2 is a regulator of in vivo insulin sensitivity and a potential target in diabetes drug development.…”
Section: Mfn2 Deficiency Causes Er Stress and Activates Jnk In Liver Andsupporting
confidence: 85%
See 1 more Smart Citation
“…Here, we demonstrate that Mfn2 deficiency in mice induces susceptibility to develop insulin resistance in response to both age and HFD treatment. These data fit with the observations that muscle Mfn2 is repressed in human obesity or in type 2 diabetes (13,14) and allow us to propose that Mfn2 is a regulator of in vivo insulin sensitivity and a potential target in diabetes drug development.…”
Section: Mfn2 Deficiency Causes Er Stress and Activates Jnk In Liver Andsupporting
confidence: 85%
“…Mfn2 is relevant in human disease, and mutations in Mfn2 have been reported in patients affected by Charcot-Marie-Tooth neuropathy type 2A (10)(11)(12). In addition, we have reported that Mfn2 expression is reduced in skeletal muscle of obese subjects and in type 2 diabetic patients (13,14).…”
mentioning
confidence: 81%
“…Previous data from our laboratory have suggested that the capacity of the OZ soleus muscle to undergo hypertrophy in response to increased loading is diminished compared with that observed in the lean Zucker (LZ) rat. Why metabolic syndrome may affect the hypertrophic response of muscle is not clear although we and others have noted that insulin resistance is associated with differences in the ability of skeletal muscle to activate intracellular signaling cascades in response to alterations in contractile activity (14,19,20,34).…”
mentioning
confidence: 99%
“…Inhibition of mitochondrial fission has been shown to inhibit muscle loss during fasting (11,15). In addition, downregulation of Mfn2 has been observed in the muscle of obese and non-obese type 2 diabetic subjects (16,17), and decreased mRNA expression levels of Mfn2 were observed in the skeletal muscle of tumor-bearing mice with severe cachexia (11). These results suggested that Mfn2 is involved in muscle wasting associated with diseases such as cancer cachexia.…”
mentioning
confidence: 99%